AB0163 Increased eryptosis levels in erythrocytes treated with antibodies from aps patients: eryptosis as new actor in aps pathogenesis. (12th June 2018) - Vomero, M.; Ceccarelli, F.; Finucci, A.; Barbati, C.; Colasanti, T.; Pensa, C.; Spinelli, F. R.; Perricone, C.; Novelli, L.; Massaro, L.; Mauro, F. R.; Foà, R.; et al.
Abstract : Background: Erythrocytes (RBCs) are highly sensitive cells constantly exposed to several stress stimuli including inflammatory mediators. Despite the absence of nuclei and the lack of crucial elements in the machinery of apoptosis, they have developed a rapid self-destruction process called eryptosis. During this process the externalization of phosphatidylserine (PS) activates the correct elimination of erythrocytes by phagocytes preventing inflammation and intravascular hemolysis. It has been recently demonstrated that PS-exposing erythrocytes are able to adhere to endothelial cells causing an impairment of circulation, 1 suggesting a possible involvement of eryptosis in the increased risk of thrombotic episodes typical of antiphospholipid syndrome (APS). Objectives: Enhanced eryptosis is known to contribute to several pathological conditions but the role of this process in APS has not been investigated yet. For this reason, we evaluated the effect of antibodies (Abs) purified from APS patients and healthy subjects positive for antiphospolipid antibodies without clinical manifestations (aPL carriers) on eryptosis activation. Moreover, spontaneous eryptosis levels in APS, aPL carriers, autoimmune haemolytic anaemia (AIHA) and healthy donors (HD) were analyzed. Methods: 30 patients with primary APS (M/F 7/23, mean age 50.5±8.2 years), 17 aPL carriers (M/F 4/13, mean age 48.6±8.3 years) were recruited after written informed consent. Moreover 13 AIHA patients and 17 HD were also enrolled as positive and negative control group respectively. Ammonium sulfate precipitation is used to purify Abs from sera of APS and aPL carriers subjects. RBCs, isolated from whole blood by centrifugation, were incubated with APS and aPL carriers Abs at concentration of 20ug/mL and after 4 hours the percentage of annexin V-positive cells (PS-exposing cells) was analyzed by flow cytometry. The same technique was used to estimate spontaneous eryptosis levels in all cohorts studied. Results: In vitro Abs from APS induced eryptosis in RBCs isolated from HD after 4 hours of culture compared to untreated and RBCs stimulated with Intravenous Immunoglobulins (IVIG), both p= 0.02. On the contrary, Abs from aPL carriers had no effect on the percentage of PS-exposing RBCs (figure 1). Ex vivo, APS patients showed higher levels of spontaneous eryptosis compared to HD (p=0.001). As expected, eryptosis was upregulated in AIHA patients compared to all populations studied (p<0.0001). Interestingly, the percentage of annexin V- positive RBCs was lower in aPL carriers respect to APS patients (p=0.001). No significant correlation between eryptosis and clinical parameters was found. Conclusions: In this study we demonstrated a new aspect of APS pathogenesis based on the capacity of Abs isolated from APS patients, and not those from aPL carriers, to stimulate eryptosis suggesting a possible contribution of this process in APS clinical manifestations. Reference: [1] Borst O, Abed M, Alesutan I, et al. Dynamic adhesion of eryptotic erythrocytes to endothelial cells via CXCL16/SR-PSOX. Am J Physiol Cell Physiol 2012;302:C644–51. Disclosure of Interest: None declared